Customer loyalty in the culinary product market: The role of satisfaction in mediating the relationship between service quality, product value, and pricing - Kurniawan, Satunggale; Rahman, Muhammad Afifi (Journal of Economic, Business & Accounting Research, 2025)
Background: This study aims to analyze the influence of service quality, product quality, price, and customer satisfaction on customer loyalty in the cooking spices industry, with a case study of Lilik Rochim (LLR) Cooking Spices consumers in Sidoarjo. Increasingly tight competition in this industry requires producers to understand the factors that influence customer loyalty in order to maintain market share. Methods: This study uses a quantitative approach with a survey method involving 90 respondents who are LLR Cooking Spices customers. The collected data were analyzed using multiple linear regression to identify the relationship between the independent variables (service quality, product quality, price, and customer satisfaction) with the dependent variable (customer loyalty). Findings: The results of the study indicate that service quality, product quality, and price have a positive and significant influence on customer loyalty. In addition, customer satisfaction acts as a mediator that strengthens the relationship between service quality, product quality, price, and customer loyalty. Thus, improving service quality, providing high product quality, and setting competitive prices can increase customer satisfaction, which ultimately has an impact on increasing customer loyalty. Conclusion: These findings have strategic implications for cooking spices producers in designing effective marketing policies to increase customer loyalty. Novelty/Originality of this article: This study uniquely examines the mediating role of customer satisfaction in linking service quality, product quality, and price to customer loyalty within the context of the Indonesian cooking spices industry.